2018
DOI: 10.1021/acsomega.8b00975
|View full text |Cite
|
Sign up to set email alerts
|

Image-Guided Development of Heterocyclic Sulfoxides as Ligands for Tau Neurofibrillary Tangles: From First-in-Man to Second-Generation Ligands

Abstract: Positron emission tomography (PET) imaging of misfolded protein aggregates that form in neurodegenerative processes of the brain is key to providing a robust marker for improved diagnosis and evaluation of treatments. We report the development of advanced radiotracer candidates based on the sulfoxide scaffold found in proton pump inhibitors (lansoprazole, prevacid) with inherent affinity to neurofibrillary tangles in Alzheimer’s disease and related disorders (e.g., dementia with Lewy bodies and the frontotempo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 38 publications
(75 reference statements)
1
24
1
1
Order By: Relevance
“…Interestingly, Rafique et al reported the logD of a number of CF3CH2OAr/FCH2CH2OAr matched molecular pairs (not shown), with Ar representing 4-pyridyl rings having a range of (non-conjugated) substituents, in which the trifluoromethylated derivative is not always the most lipophilic one although all compounds are within a narrow lipophilicity range 40. …”
mentioning
confidence: 99%
“…Interestingly, Rafique et al reported the logD of a number of CF3CH2OAr/FCH2CH2OAr matched molecular pairs (not shown), with Ar representing 4-pyridyl rings having a range of (non-conjugated) substituents, in which the trifluoromethylated derivative is not always the most lipophilic one although all compounds are within a narrow lipophilicity range 40. …”
mentioning
confidence: 99%
“…24 With the aim of repurposing the lansoprazole scaffold for tau PET, we recently reported the radiosynthesis and pre-clinical evaluation of lansoprazole derivatives, including [ 18 F]N-methyl lansoprazole ([ 18 F]NML), as potential tau imaging agents. 25,26,27 , These studies demonstrated that [ 18 F]NML has high affinity for heparin-induced tau filaments (K d = 0.7 nM) and 11.7-fold selectivity for tau over amyloid. This selectivity could perhaps be better, but an order of magnitude is in line with the 20-fold selectivity that has been suggested as a target for the ideal tau radiotracer.…”
Section: Introductionmentioning
confidence: 90%
“…[ 18 F]NML is synthesized from the gem-difluoro enol ether precursor 1 using no-carrieradded [ 18 F]KF in the presence of [2.2.2]cryptand (kryptofix® 222, crypt-222), and a proton source (iPrOH or NH 4 Cl) to quench the reaction and allow generation of the trifluormethyl group, as previously reported (Scheme 1). 25,27,29 These prior syntheses provided [ 18 F]NML suitable for preclinical use but, in order to prepare [ 18 F]NML for clinical use, a radiosynthesis compliant with current Good Manufacturing Practice (cGMP) needed to be validated. During our initial studies, we found that formation of high molar activity [ 18 F]trifluoromethyl groups can be challenging because of isotopic exchange as well as fluoride ion release through precursor degradation.…”
Section: Validation Of the Radiosynthesis Of [ 18 F]nmlmentioning
confidence: 99%
See 1 more Smart Citation
“…此外, 亚磺酰基是羰基的生物等排体 [19] , 在药物结 构设计和改造中也有着广泛的应用, 例如可用于提高药 物分子的水溶性, 影响药物代谢动力学性质, 增强药物 与靶标蛋白的相互结合能力等. 1 [1] 2 [2] 3 [3] 4 [4] 5 [5] 6 [12] 7 [14] R [16][17][18] -amanitin 另外, 研究发现, 兰索拉唑 13 及其衍生物与可能导 致阿尔兹海默症等神经退行性疾病的 Tau 神经原纤维缠 结(Neurofibrillary tangles, NFTs), 具有较高的体外亲合 力(IC 50 : 10 -8 ~10 -10 mol/L) [20] . 因此, [ 18 化为较为稳定的阿焦烯(Ajoene, 18)以及其它有机硫化 物(Scheme 2) [21] .…”
unclassified